Structural studies of the PIR and RIFIN families from malaria-infected erythrocytes - Harrison, TE (2020)
Malaria, caused by the Plasmodium parasite, is responsible for the deaths of close to half a million people a year. During the course of infection, the parasite invades and remodels the host red blood cell, often requiring the export of a number of proteins to the erythrocyte surface. These include the RIFIN family of Plasmodium falciparum, which have been shown to directly modulate the host immune response through interactions with inhibitory immune receptors such as LILRB1 and LAIR1. Additionally, the PIR family of a number of human- and rodent-infective Plasmodium species have been implicated in the determination of parasite virulence and the outcome of infection, along with cytoadhesion of infected erythrocytes to the vasculature. Here, I present the structure of the variable region of a RIFIN in complex with LILRB1. This is the first structure of any member of the RIFIN family and reveals that the RIFIN utilises a conserved mode of binding, which can be blocked through a single mutation in all RIFINs tested, and which mimics the interaction of MHC class I, the native ligand of LILRB1. The RIFIN is also able to mimic the effect of MHC binding both on signalling through LILRB1, and on inhibition of NK cell activation at the immunological synapse. I also present the structure of the extracellular domain of a PIR protein from Plasmodium chabaudi, the first for a member of this family, revealing a novel α-helical fold. Sequence analysis and homology modelling show conservation of this fold across PIRs from 4 human- and 3 rodent-infective Plasmodium species, as well as excluding the RIFINs and STEVORs from membership of the PIR family. These findings provide both a molecular mechanism for RIFIN function, along with a structural definition of the PIRs, giving valuable insight into 2 major families of Plasmodium variant surface antigens.